Implementation And Effectiveness of Copyright In Law No. 28 of 2014 And MUI Fatwa No. 5 of 2005 - Aminudin Ma'ruf; Muhammad Faisal Hamdi; Rashifahunnisa' Mellinia; Imron Rosyadi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
The development of Islamic literacy in Indonesia shows the capability of the nation in competing with other Muslim nations. However, copyright is often neglected by many parties. The study aims to assess the implementation and effectiveness of the copyright in law No. 24 of 2014 and MUI Fatwa No. 5 of 2005. A qualitative methodology has been conducted with the approach of literature and field study. The data was obtained through interviews and observations with 3 academic authors and 9 non-academic authors. The results of the study indicate that the majority of the academic authors argue that there is a lack of enforcement and impact in the law and fatwa. Similarly, the other authors carry the same opinion with some highlights on its effectiveness. The paper suggests that policymakers intensify the implementation and effectiveness of copyright law and fatwa in Indonesia. The enforcement of the law and fatwa will lead to the prosperity of authors and lead to a knowledgeable society. The study keenly expects future studies in the field to cover more samples with different methodologies.